(3x-x)+(8x+9)=

Simple and best practice solution for (3x-x)+(8x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-x)+(8x+9)= equation:


Simplifying
(3x + -1x) + (8x + 9) = 0

Combine like terms: 3x + -1x = 2x
(2x) + (8x + 9) = 0
(2x) + (8x + 9) = 0

Reorder the terms:
(2x) + (9 + 8x) = 0

Remove parenthesis around (9 + 8x)
(2x) + 9 + 8x = 0

Reorder the terms:
9 + (2x) + 8x = 0

Combine like terms: (2x) + 8x = 10x
9 + 10x = 0

Solving
9 + 10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 10x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 10x = 0 + -9
10x = 0 + -9

Combine like terms: 0 + -9 = -9
10x = -9

Divide each side by '10'.
x = -0.9

Simplifying
x = -0.9

See similar equations:

| x^3-2x^2+36=0 | | 4(5x-8)-13x=24 | | (12y*12y-144)=(3y*3y) | | x^2+(6x+17)=0 | | n+6-2=1 | | 2+c-3=3 | | X^4-3x^2+4x-6=0 | | F(x)=-3x+5 | | (cd+2)+cd-4= | | x^2-(m+1)x-5=0 | | (8x+4)=(5x+2) | | Sinx=0.75 | | 2a+16+b=18+b | | 9x+26x^2=3 | | 6y-2=2y+7 | | 8+3x+x=20 | | 58474+46274= | | t=5(2)+3(4) | | 15-3x+2-8x=39 | | 58584839748375097+85574758475398= | | 7x-5y+(-3x+-4y)= | | M(m+2)=2 | | 5x-13=-25 | | 13y^2-4y-9=0 | | 4w=w-2 | | 13y^2-4y+9=0 | | x^2+y^2=4x-4y-6 | | 40+7x=0 | | 0.3*x+x^2=0.3x^3 | | (3c-2)(2c+5)=0 | | x^2+y^2-4x+4y+6=0 | | (45x^6)-(36y^2)-144=0 |

Equations solver categories